Web Portal Development for V-KES Teaching Factory at Politeknik Negeri Jember - Mudafiq Riyan Pratama; Gamasiano Alfiansyah; Demiawan Rachmatta Putro Mudiono; Selvia Juwita Swari (P3M Politeknik Negeri Jember, 2026)
V-Kes serves as a Teaching Factory (TeFa) for the Health Information Management Study Program within the Department of Health. Based on a preliminary study, it was found that V-Kes does not yet have a web portal specifically designed for early detection and integrated information services related to Diabetes Mellitus (DM). This study aims to develop a novel web-based portal that integrates early DM detection features with an educational and service information platform for the V-Kes TeFa, distinguishing it from existing general health web portals. The study focuses on the system outcomes and its impact on users rather than detailed development processes. The system was implemented as a web portal, with the frontend developed using React and Vite, and the backend utilizing Laravel. The study involved five V-Kes TeFa managers as informants for user identification and system evaluation. User satisfaction evaluation was conducted using qualitative methods supported by structured feedback indicators, including usability, information quality, and system responsiveness. Data were analyzed through data reduction, data presentation, and conclusion drawing. The study resulted in the development of a web-based portal at the V-Kes TeFa that enables early DM risk screening through user input data and provides real-time health information access. Evaluation results indicate that most users found the system easy to use, informative, and relevant to their needs, although specific issues were identified in system response time. However, improvements are still required in the timeliness dimension to provide faster response times according to user needs, as well as the addition of a user manual. Therefore, future development will focus on enhancing system access speed and incorporating a manual book.